Significance of non-monetary forms of capital: importance of social capital - (:unkn) unknown (Springer, 2020)
There exists non-monetary forms of capital, which are utterly important for better economic performance. However, the non-monetary forms of capital are usually either neglected by or unknown to managers. In sum, their significance is almost always overlooked. This article scrutinized one such important non-monetary capital, the social capital. Social capital is a vague term which is broadly used by economists to refer to the social associations and relations between individuals, groups and institutions in an economy. According to a popular classification, it is possible to classify social capital into three classes. These three classes namely are the bonding, bridging and linking social capital classes. While bonding and bridging capital refer to horizontal social relations between constituents with no hierarchical positioning against each other, linking capital reflects a vertical structure and mostly refers to the relations of individuals and social groups with formal institutions. Empirical studies have shown that high levels of social capital stock is usually beneficial in the economic sense. However, too much bonding capital might have adverse economic impact as well. Bonding capital includes our relations with and associations to the others in our closest circle. It includes the social relations and networks established between the closest friends, kins etc. That is why so strong bonding feelings may lead us to making favors to others in our bonding circle even when such favors reflected worse than optimal choices from the pure economic rationale. Nepotism or favoritism, as two examples, may result in job offers to people with whom we are bonded but not so talented in fact. That said, social capital, especially the bridging and linking types, have the capacity to make positive economic contributions to the society through enabling efficient buildup of teams, facilitating idea sharing, reducing contract costs, boosting productivity, mitigating informational asymmetry issues and supporting entrepreneurial activities. © Springer Nature Switzerland AG 2020.